Left ventricular mechanics after arterial switch operation: a speckle-tracking echocardiography study. Issue 3 (March 2016) - Di Salvo, Giovanni; Bulbul, Ziad Al; Issa, Ziad; Fadel, Bahaa; Al-Sehly, Abdullah; Pergola, Valeria; Halees, Zohair Al; Fayyadh, Majid Al
Abstract : Background: The arterial switch operation (ASO) is nowadays the standard procedure for the repair of dextro-transposition of the great arteries (d-TGA). Reduced exercise capacity, coronary artery abnormalities, and reversible myocardial perfusion defects have been demonstrated in patients who have undergone ASO. Despite this, indices of systolic function, assessed by standard echocardiography, are within the normal range. Speckle-tracking echocardiography (STE) can detect early subclinical myocardial abnormalities in several diseases even in the presence of normal left ventricular (LV) ejection fraction. Aim: To assess LV systolic myocardial deformation and torsion in asymptomatic ASO patients with normal LV ejection fraction (≥55%) by using STE. Methods: We studied 62 asymptomatic patients (26 women) who have undergone single-stage ASO for simple d-TGA, aged 8.5 ± 5.7 years, with a normal LV ejection fraction (≥55%); 31 age and sex comparable controls (14 women), aged 7.9 ± 4.9 years. Results: In patients who have undergone ASO, global LV longitudinal strain was significantly lower than that in controls (−19.2 ± 2.9% vs. −22.7 ± 2.4%, respectively, P < 0.0001). Longitudinal deformation was significantly impaired in the anterior and both anterior and posterior septal walls. In patients who have undergone ASO global circumferential strain and LV torsion were similar to controls. At multivariate analysis global LV longitudinal strain was significantly correlated only with age at surgery ( P = 0.005). Conclusion: We demonstrated a significant reduction in longitudinal myocardial deformation correlated with the age at surgical repair, despite a normal LV ejection fraction, in the largest series of asymptomatic ASO patients by using STE. Our findings suggest early (⩽7 days) operation on d-TGA patients and continued monitoring of ventricular function by STE.